Implementation of a Decision Support System in Determining Scholarship Recipients Using the MOORA Method at STMIK Mulia Darma - Chandra Frenki Sianturi (Universitas Budi Darma, 2025)
The scholarship recipient selection process often faces challenges such as subjectivity, time constraints, and a lack of transparency in decision-making. To address these issues, this study developed a web-based decision support system that implements the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method. This system is designed to assist scholarship administrators in determining recipients objectively and efficiently by considering several criteria, namely GPA, parental income, number of dependents, and non-academic achievements. The research was conducted using a quantitative approach that included the stages of problem identification, data collection, criterion weight determination, data normalization, calculation of Yi preference values, and alternative ranking. The results of the system implementation indicate that the MOORA method can provide accurate rankings based on the combination of criterion weights and the value of each alternative. This system not only accelerates the selection process but also enhances transparency and accountability in decision-making. In conclusion, the application of the MOORA method in the scholarship decision support system contributes significantly to a fair, structured, and accountable selection process.